2020
DOI: 10.3390/rs12020255
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Semantic Gap between Land Tenure and EO Data: Conceptual and Methodological Underpinnings for a Geospatially Informed Analysis

Abstract: When spatial land tenure relations are not available, the only effective alternative data method is to rely on the agricultural census at the regional or national scale, based on household surveys and a participatory mapping at the local scale. However, what if even these are not available, which is typical for conflict-affected countries, administrations suffering from a lack of data and resources, or agencies that produce a sub-standard quality. Would it, under such circumstances, be possible to rely on remo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 60 publications
1
11
0
Order By: Relevance
“…Third, Lee and de Vries [34] seek to bridge the semantic gap between land tenure concepts and remotely sensed or earth observation (EO) data. Specifically, they investigate the circumstances where it is possible to rely on EO data to inform land administration applications, such as cadastral mapping and land use change monitoring.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Third, Lee and de Vries [34] seek to bridge the semantic gap between land tenure concepts and remotely sensed or earth observation (EO) data. Specifically, they investigate the circumstances where it is possible to rely on EO data to inform land administration applications, such as cadastral mapping and land use change monitoring.…”
Section: Overview Of Contributionsmentioning
confidence: 99%
“…Along with the growth of remote sensing applications in SES, there has been growing recognition and evidence of the vital links between remote sensing and land administration [12][13][14][15][16][17][18][19]. Geospatial data has emerged as powerful source of information for enabling both socio-technical assessment [20] and socio-legal analysis [21] in land administration sphere. Moreover, recent advancements have led to a renewed interest in identifying socio-spatial footprints of land boundaries and associated land rights through integration of different sets of geospatial and socio-economic data and informative interpretation [12,21].…”
Section: Introductionmentioning
confidence: 99%
“…Geospatial data has emerged as powerful source of information for enabling both socio-technical assessment [20] and socio-legal analysis [21] in land administration sphere. Moreover, recent advancements have led to a renewed interest in identifying socio-spatial footprints of land boundaries and associated land rights through integration of different sets of geospatial and socio-economic data and informative interpretation [12,21]. Thus, a novel approach to land administration sheds a contemporary light on grounded theories and practices of land tenure, use, value, development, and governance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, by increasing the spatial, spectral, and temporal resolutions of the remote sensing images as well as new tools to acquire data, the available objects and features for solving the puzzles will increase and lead to developing robust proxies. Already the results of this review were used by researchers to address the identified gaps (Castañeda-Garza et al 2019;Hodicky et al 2020) and develop new remote sensing-based proxies or combine them to address DRM (Derakhshan et al 2020), and even using the term "proxy" as defined in this study in other domains rather than DRM (Lee and De Vries 2020). The proposed conceptual framework in Chapter 3 comprehensively addresses the aim of recovery assessment based on remote sensing data.…”
Section: Reflections and Outlookmentioning
confidence: 99%